Exposure to fine particulate matter and hospital admissions due to pneumonia: Effects on the number of hospital admissions and its costs - Patto, Nicole Vargas (2016)
Objective: Given that respiratory diseases are a major cause of hospitalization in children, the objectives of this study are to estimate the role of exposure to fine particulate matter in hospitalizations due to pneumonia and a possible reduction in the number of these hospitalizations and costs. Method: An ecological time-series study was developed with data on hospitalization for pneumonia among children under 10 years of age living in São José do Rio Preto, state of São Paulo, using PM2.5 concentrations estimated using a mathematical model. We used Poisson regression with a dependent variable (hospitalization) associated with PM2.5 concentrations and adjusted for effective temperature, seasonality and day of the week, with estimates of reductions in the number of hospitalizations and costs. Results: 1,161 children were admitted to hospital between October 1st, 2011, and September 30th, 2013; the average concentration of PM2.5 was 18.7 μg/m3 (≈32 μg/m3 of PM10) and exposure to this pollutant was associated with hospitalization four and five days after exposure. Conclusion: A 10 μg/m3 decrease in concentration would imply 256 less hospital admissions and savings of approximately R$ 220,000 in a medium-sized city.